AB0829 Demographics of Patients with New-Onset Psoriatic Arthritis: Real Life Data from an Inception Cohort. (9th June 2015) - Kalyoncu, U.; Yılmazer, B.; Bayındır, Ö.; Aksu, K.; Dalkılıç, E.; Öksüz, M.F.; Tarhan, E.F.; Can, M.; Küçükşahin, O.; Kimyon, G.; Akyol, L.; Onat, A.M.; et al.
Abstract : Background: Psoriatic arthritis is a complex disease with a wide range of manifestations. In this inception cohort of PsA patients we aimed to identify the initial manifestations as well as disease activity characteristics and compare with an unselected group of patients with longstanding disease. Methods: PsART (Ps oriatic A rthritis R egistry of T urkey) is a prospective, multicentre study in Turkey on patients with PsA. Patients are consecutively recruited to this registry. Patients who have been newly diagnosed with PsA have been identified, and their characteristics were compared with longstanding disease. Results: Within 746 patients recruited, 111 (14.9%) had a new diagnosis for PsA. Patients in the inception cohort were significantly younger than the rest of the cohort (p=0.03) (table ). Females were 53.2% of the inception and 66.8% of the non-inception cohort (p=0.007). For types of joint patterns, 14.4% of the inception cohort had only axial involvement whereas this was seen in 8.2% for the other group (p=0.05). The other joint patterns were comparable among groups. Both groups had similar tender and swollen joint counts, BASDAI and BASFI. Patient (p=0.002) and physician global assessments (p<0.001), fatigue (p=0.02), duration of morning stiffness (p=0.02) and CRP (p=0.05) were higher in the inception cohort. Female patients had higher patient global assessment and fatigue scores despite similar physician global assessment, swollen and tender joint counts, BASDAI, BASFI and CRP with males in non-inception cohort. For the inception cohort, there were no differences between the 2 genders. Conclusions: More patients present with sole axial involvement at the beginning, which may explain the higher disease activity agreed by the patient and the physician despite similar tender and swollen joint counts. Females may have a different perception of the disease with worse patient global assessments and fatigue in longstanding disease. Disclosure of Interest: None declared